PENGGUNAAN TEPUNG LIMBAH PENGALENGAN IKAN DALAM RANSUM TERHADAP KUALITAS KARKAS BROILER - Gombo, Etias; Najoan, M.; Wolayan, F. R.; Imbar, M. R. (Universitas Sam Ratulangi, 2015)
USE OF WASTE CANNING MEAL IN THE QUALITY OF CARCASS BROILER RATION. A research evaluating the effects of the utilization of fish meal based on canned fish waste product of fish processing plant in Bitung, Nort Sulawesi. This research used 60 broiler day old chick. The research had been conducted for 42 days. Completely Randomized Design (CRD) will 4 treatments and 5 replications was used the treatments were sereal level of canned fish waste product :R1 = 8%, R2 = 10%, R3 = 12%, R4 Â= 14%. Variables measured was carcass quality crusisting of carcass percentage, abdominal fat percentage, and liver percentage. The results showed that there were no significant differences (P>0.05) on carcass percentage (71,13-72,90%) and liver percentage (1,82-2,22%); Howerer there was significant differences (P<0.05) on abdominal fat. Honestly significant difference (HSD) testÂ thormed that abdominal fat percentage of broiler fed 8% fish canned fish by product (3,27%) was significanly (P<0.05) higher than broiler fed 10% (2,76%) and 12% (2,75%), there was no significant difference between R2 and R3, However significantly higher than broiler fed 14% canned fish by product (1,84%). It can be concluded that the utilization of canned fish meal by product up to 14% in the ration can produce a good quality carcass. Â Key words: Fish meal, canned fish by product, carcass quality